Effect of temperature, water loading, and Ru/C catalyst on water-insoluble and water-soluble biocrude fractions from hydrothermal liquefaction of algae. (September 2017) - Xu, Donghai; Savage, Phillip E.
Highlights: Studied separately water-insoluble bio-oil and that extracted from the aqueous phase. Ru/C can be used to vary the yields of water-soluble and water-insoluble biocrude. HTL temperature influences the yields of water-soluble and water-insoluble biocrude. Abstract: Hydrothermal liquefaction (HTL) converts algal biomass into a crude bio-oil (biocrude) and aqueous-phase products. The effect of temperature, water loading, and added H2 and/or Ru/C catalyst on the properties of the biocrude that spontaneously separates from the aqueous phase post reaction and also the biocrude that is extractable from the aqueous phase by dichloromethane is explored herein. This report is the first to elucidate how the yields, compositions, heating values, and energy recoveries of the two biocrudes vary with the processing conditions above. Increasing temperature from 350 to 400 °C increased the yield of water-insoluble biocrude (38.1–42.5 wt%) and its hexane-soluble subfraction (63.7–85.6 wt%) while decreasing the yield of extractable, water-soluble biocrude (6.6–2.5 wt%). The Ru/C catalyst had the same effect. Reaction temperature and catalysts could be used to manipulate the proportions of water-soluble and water-insoluble biocrude from algae HTL and thereby manipulate biocrude quantity and quality.